FINANCING POLICY OF FIRMS IN THE CONTEXT OF CRISIS-INDUCED VULNERABILITIES - Tudose, Mihaela Brindusa; Rusu, Valentina Diana (Studies and Scientific Researches. Economics Edition, 2017)
Our study analyses the changes in the financial structure of the firms in the context of the vulnerabilities induced by the financial crisis. The study show that there have been registered a reconfiguration of firms’ financial structure which has triggered an increase in their financial fragility and vulnerability to crises. The results obtained confirm that the effects of financing differ depending on the economic conditions in particular period (normal periods and crisis periods). In tranquil times solvency is more important for the firms than liquidity. After crisis, the firms became more cautious regarding liquidity, solvency and the prospect of securing long-term financial balance. These firms have abandoned the objective of maximizing the positive effects of debt financing adopting a more prudent financing.